Lime kilns in Beja and associated activities: Beyond materials in the conservation of Cultural Heritage - Marluci Menezes (Conservar Património, 2016)
The Laboratório Nacional de Engenharia Civil and the Municipality of Beja started a technical and scientific collaboration in order to contribute to inventorying and safeguarding the lime ovens – and associated activities – as intangible heritage. The aim of this cooperation and the progress already achieved are presented in broad lines. Considering Cultural Heritage conservation policies, the interest of a work perspective in the interface between material and immaterial is highlighted.